Comportamiento defensivo de la "Rana Ternero", Leptodactylus pentadactylus - Villa, Jaime (Revista de Biología Tropical, 1967)
A "defense-fight reaction" previously unknown in the genus Leptodactylus is described and illustrated for L. pentadactylus. The defense consists of the inflation of the body, raised on the stiffened legs, and the emission of certain hissing sounds. It is similar to that ohserved in Bufo alvarius, B. bufo and B. viridis. Other defenses of the same species, and of other species of the genus, are briefly reviewed.